L9 Curcumin: a natural compound to counteract the pathology of huntington's disease?. (13th September 2016) - Elifani, Francesca; Crispi, Stefania; Filosa, Stefania; Castaldo, Salvatore; Capocci, Luca; Madonna, Michele; Amico, Enrico; Pompeo, Giovanni; Pompeo, Francesco; Brunetti, Alexandra; Ruggieri, Stefano; Maglione, Vittorio; et al.
Abstract : Background: Curcumin, the active ingredient in turmeric, has been validated to harbour important beneficial effects for a multitude of inflammatory-based diseases and also for neurodegenerative processes similar to those occurring in HD. To this regard, it has been recently described that curcumin significantly improves neuropathology and positively affects some of the neurochemical and neurobehavioral disease-related defects in a mouse model of HD. Although the mechanism of its neuroprotective action is still not completely understood, it has been hypothesised to act majorly through anti-inflammatory and anti-oxidative activities. Aim: Here, our purpose is to investigate whether such specific properties of curcumin may potentially play a role in the control of the gradual body weight loss and in the accumulation of redox metals commonly observed in HD. We also want to examine whether the described beneficial effect of curcumin in HD is a shared mechanism across multiple HD models and not confined only to a single or few systems. Methods: Curcumin along with bioperine (bioavailability enhancing-agent) was orally administered to females 10 days before pregnancy and during the entire gestation period up to the end of lactation. Starting from the third week of age, pups were daily treated with 40 mg/kg curcumin for 7 weeks. Results: In line with other studies, so far, our preliminary data confirmed that curcumin has an outstanding safety profile with no adverse effect also in R6/2 mice. Evaluation of any potential beneficial effects of the treatment is in progress. Conclusion: Curcumin is well tolerated also in R6/2 HD mice and, based on its therapeutic properties, it could conceivably represent an attractive possibility to develop a valuable dietary supplement in neurodegenerative diseases such as HD.